2016
DOI: 10.1111/pbr.12411
|View full text |Cite
|
Sign up to set email alerts
|

Oligogenic control of resistance to soil‐borne viruses SBCMV and WSSMV in rye (Secale cereale L.)

Abstract: Rye production in European growing areas is constrained by the soilborne cereal mosaic virus (SBCMV) and the wheat spindle streak mosaic virus (WSSMV). To date, no European rye cultivars are known to exhibit resistance against these viruses. In this study, we pursued a quantitative trait locus (QTL) mapping strategy to identify genomic regions for resistance to SBCMV and WSSMV in rye. Three populations, each comprising 100 lines segregating for resistance to SBCMV and/or WSSMV, were evaluated for disease respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Both earlier screenings of rye genomes and the current study indicate that little genetic variability can be expected in adapted rye (Secale cereale), although rye generally shows a high degree of variability as it is a typical open-pollinator. The first studies by Erath et al (2016) as well as the present results show that significant resistance can only be found in wild rye, particularly in the perennial Secale montanum and S. africanum as well as within the annual S. vavilovii. While S. montanum and S. africanum belong to the genome complex of S. strictum, S. vavilovii syn.…”
Section: Screeningsupporting
confidence: 73%
See 2 more Smart Citations
“…Both earlier screenings of rye genomes and the current study indicate that little genetic variability can be expected in adapted rye (Secale cereale), although rye generally shows a high degree of variability as it is a typical open-pollinator. The first studies by Erath et al (2016) as well as the present results show that significant resistance can only be found in wild rye, particularly in the perennial Secale montanum and S. africanum as well as within the annual S. vavilovii. While S. montanum and S. africanum belong to the genome complex of S. strictum, S. vavilovii syn.…”
Section: Screeningsupporting
confidence: 73%
“…Also in the experiment carried out by Erath et al (2016), no resistance genes have so far been identified that can be used in rye breeding. Additional characterization of the DNA segment on chromosome 2R therefore offers the chance to describe such a gene and to create suitable markers for it.…”
Section: Molecular Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies involving the QTL mapping of other minor and pseudo-cereals, however, are relatively limited and mostly include studies in rye (Erath et al 2016, Miedaner et al 2018, Myśków et al 2018, Wang et al 2015, oat (Admassu-Yimer et al 2019, Babiker et al 2015, Pellizzaro et al 2016, Schneider et al 2015, Sunstrum et al 2018, Zimmer et al 2018, and millet. Of the various types of millet, pearl millet (Ambawat et al 2016, Aparna et al 2015, Kumar et al 2016b, 2018, Pucher et al 2018, Punnuri et al 2016, Taunk et al 2018 and foxtail millet (Fang et al 2016, Mauro-Herrera and Doust 2016, Ni et al 2017, Odonkor et al 2018, Wang et al 2017a, 2017b have received the majority of research attention, although one study also focused on proso millet (Rajput et al 2016).…”
Section: Biparental Qtl Mappingmentioning
confidence: 99%